2017
DOI: 10.1123/jsr.2015-0215
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Cryotherapy on Muscle Strength and Shoulder Proprioception

Abstract: Context: A common intervention used by clinicians, cryotherapy poses several benefits in managing acute injuries. However, cooling muscle tissue can interfere with muscular properties and the sensory-motor system. Objective: The aim of this study was analyse the influence of cryotherapy with a crushed-ice pack on shoulder proprioception concerning joint position sense, force sense, the threshold for detecting passive movement, and maximal force "The Acute Effect of Cryotherapy on Muscle Strength and Shoulder P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
1
0
4
Order By: Relevance
“…Üst ekstremite için kriyoterapinin akut etkisinin değerlendirildiği çalışmalarda propriyosepsiyon, kas kuvveti ve atış doğruluğu incelenmiştir. 2,17 Bu çalışmalarının sonuçları kriyoterapinin negatif etkisini göstermektedir. Wassinger ve ark.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Üst ekstremite için kriyoterapinin akut etkisinin değerlendirildiği çalışmalarda propriyosepsiyon, kas kuvveti ve atış doğruluğu incelenmiştir. 2,17 Bu çalışmalarının sonuçları kriyoterapinin negatif etkisini göstermektedir. Wassinger ve ark.…”
Section: Discussionunclassified
“…48 sağlıklı kadında yaptıkları çalışmalarında, 15 dk buz paketi uygulanması sonucu omuz propriyosepsiyonunun ve kas kuvvetinin azaldığını bul-muşlardır. 17 Propriyosepsiyondaki azalmayı kriyoterapi ile kas iğciklerinin duyarlılığının azalmasına bağlamışlardır. Dokuların viskoelastisitesinin kriyoterapi ile değiştirilebilmesi, kas iğciklerinin aktivasyonunda azalmaya neden olmakta ve sonuç olarak kas kuvvet üretimi de azalmaktadır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, other studies have revealed that the JPS did not change after cryotherapy (4,5). Recently, some studies have indicated that local cooling does not affect proprioceptive acuity of the healthy knee joint (11,12); however, other studies have demonstrated that the application of crushed ice to the knee and shoulder has an adverse effect on knee joint repositioning during the descent phase of a small knee bend (13) and shoulder joint repositioning (14). Therefore, data regarding the effects of cryotherapy on the repositioning error has remained con-tradictory.…”
Section: Introductionmentioning
confidence: 99%
“…또 한 근피로는 관절의 위치와 관련된 고유 수용성 감각의 민감도를 저하시키며 [3], 균형에도 영향을 미친다고 보 고하고 있다 [15]. 근피로를 감소시키기 위한 다양한 회복 방법 중 냉 처치 요법은 급성 또는 만성 손상 치료를 위한 방법으로 쉽게 적용할 수 있기에 가장 일반적인 개입 방법이다 [16]. 냉 처치 요법은 통증 역치와 조직의 점성을 증가시 키고, 신체활동을 위한 엔도르핀(endorphins)과 테스토 스테론(testosterone)을 빠르게 분비시키며, 운동으로 유 발된 피로와 스트레스를 회복시키는 작용을 한다 [17].…”
unclassified